Strategies to eradicate the paper waste in my practicum site (2019)
I did my practicum in the Caribe jewelry in the second half of the year 2018. I worked in the company as a sales consultant, mainly attending cruise groups with visitors, mostly foreigners, who came to receive a tour in the emerald museum. My job was to generate profits for the company through my language skills, previous sales preparation and knowledge of emeralds, as the jewelry's precious gemstone. To be able to make the sales it was necessary to use tools such as paper mainly to make discounts, also to make us understand with customers, first because on many occasions customers did not speak a language that sales consultants could understand and secondly because at the time to make transactions in dataphones what is going to be charged to the client must be done in Colombian pesos, figures that scare customers, so the explanation of the conversions from dollars to pesos must be done through paper. During my work as a sales consultant, I found that in all the stores of the jewelry there is an excessive use of paper, in which, although they were necessary for efficiency at the time of sales advice, represented a waste of paper that could be reused and that when discarded they contribute to the contamination of the air, water and soil by the chemical components that are used for its production. In addition to representing a negative impact on the atmosphere due to the felling of trees that are those of the main oxygen generators. Within the jewelry we did not have training in the rationalized use of paper that was used, so there is no Zero Paper policy within the company at least within the sales room, where the problem is aggravated.